Successful Management of Miliary Tuberculosis with Concomitant Anemia: A Case Report - Baharuddin Wahyu Usman; Swartawan, I Nyoman Ika Prapta; Dela Intan Permatasari; Harlina Konoras; Taufik Supriyana Trisaputra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Miliary tuberculosis (TB) is a disseminated and potentially fatal form of TB characterized by the hematogenous spread of Mycobacterium tuberculosis, often complicated by anemia of chronic disease. The diagnosis and management of miliary TB, particularly in conjunction with anemia, can be challenging, especially in resource-limited settings. Case presentation: We report the case of a 20-year-old male from a remote region in Eastern Halmahera, Indonesia, who presented with progressive shortness of breath, productive cough, night sweats, unintentional weight loss, and generalized weakness. Clinical examination revealed signs of anemia and respiratory distress. Laboratory investigations confirmed microcytic hypochromic anemia and a positive GeneXpert MTB/RIF test. Chest radiography demonstrated diffuse miliary nodules, consolidation, and cavitation, establishing the diagnosis of miliary TB with concomitant anemia. The patient received a standard six-month anti-tuberculosis therapy regimen, along with supportive care and targeted treatment for anemia and associated symptoms. The patient demonstrated significant clinical and hematological improvement, leading to discharge after 11 days of hospitalization. Follow-up assessments confirmed continued progress and the absence of complications. Conclusion: This case underscores the critical importance of maintaining a high index of suspicion for miliary TB in patients presenting with respiratory and constitutional symptoms, even in the absence of traditional risk factors. The presence of anemia can further complicate the clinical picture. Prompt diagnosis through a combination of clinical assessment, laboratory investigations, and imaging studies, followed by the immediate initiation of appropriate treatment, including the management of anemia, is paramount for achieving favorable outcomes in patients with miliary TB. The case also emphasizes the necessity for comprehensive care and follow-up to ensure sustained recovery and prevent relapse.